Green extraction methods of fucoxanthin from brown macroalgae - Marcell Gyurkač; Taja Žitek Makoter; Miha Grilc; Blaž Likozar; Željko Knez; Maša Knez Marevci (Journal of Agriculture and Food Research)
Brown macroalgae, harvested and processed at a scale of multimillion tons annually, contain fucoxanthin, a bioactive carotenoid with demonstrated anti-cancer and anti-inflammatory properties. While seaweed is primarily cultivated for food products, significant quantities of non-edible parts, still containing valuable compounds, are discarded during processing. This comprehensive review critically examines current approaches for upcycling macroalgal waste to food supplements and pharmaceuticals through the extraction of fucoxanthin, with particular emphasis on emerging green technologies and solvents, such as supercritical carbon dioxide and ionic liquids, applied individually or in combination. The article also evaluates these methods against conventional organic solvent extraction, considering extraction efficiency, solvent greenness and recyclability, process sustainability, and potential for industrial scale-up, while identifying current limitations and explore opportunities for process optimization. Despite demonstrating clear advantages over conventional organic solvents in extraction time, yield, recycling rate, and environmental safety, green solvents, especially ionic liquids, remain underutilized. This thorough analysis thus reveals critical gaps in current extraction strategies and provides evidence-based recommendations for future research directions in sustainable extraction technologies. Our findings suggest pathways for transforming macroalgal waste streams into high-value nutraceutical products, contributing to the development of circular bioeconomy approaches in marine biomass processing.